2005
DOI: 10.5858/2005-129-0645-advopb
|View full text |Cite
|
Sign up to set email alerts
|

Automatic 3-Dimensional Visualization of Peripheral Blood Slides: A New Approach for the Detection of Infection/Inflammation at the Point of Care

Abstract: Context.—The identification and quantitation of the intensity of the acute-phase response at the point of care might be of clinical relevance. Objective.—To report the possibility of automatic screening of unstained peripheral blood slides by using a 3-dimensional image analysis system. Design.—Peripheral venous blood was obtained from children with acute inflammation/infection and examined by an automatic 3-dimensional image analyzer to detect the number of white blood cells as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…• Among pediatric patients with infection and\or inflammation, n = 125 (Urbach et al 2005). • Among patients with acute ischemic neurologic events, n = 60 (Anuk et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Among pediatric patients with infection and\or inflammation, n = 125 (Urbach et al 2005). • Among patients with acute ischemic neurologic events, n = 60 (Anuk et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies noted significant reductions in erythrocyte aggregation and improved hemorheological profiles (Allegra et al 1995;Nicolaides 2003) after lowering the inflammatory state through lifestyle modifications (Raz et al 2007;Sandor US assessment of erythrocyte aggregation and inflammation • P. Gyawali et al et al 2014) or by the use of anti-inflammatory therapeutic agents (Ge et al 2016;Jiang and Lian 2015;Kelly and Dominguez 2010;Li et al 2015;Szentkereszty et al 2014). Lastly, some studies (n = 15) underscored erythrocyte aggregation as a superior or independent marker of inflammation (Anuk et al 2002;Assayag et al 2005Assayag et al , 2008Berliner et al 2002Berliner et al , 2005Gyawali et al 2016;Levin et al 2006;Maharshak et al 2002;Rotstein et al 2002a;Sharshun et al 2003;Urbach et al 2002Urbach et al , 2003Urbach et al , 2005Vayá et al 2013b) or sepsis (Yeom et al 2017). Only 1 study reported increased erythrocyte aggregation with aging and associated it with increase in inflammation (Vayá et al 2013a).…”
Section: Description Of Studiesmentioning
confidence: 99%